THE KEY ROLE OF STUDENTS' READING ATTITUDES IN COMPREHENSION SKILLS - Mira Ermita; Ida Nuraida; Halimah, Halimah (Bajang Institute, 2024)
This study was conducted to see whether or not there is a relationship between students' reading attitudes and their reading achievement. The method used in this study is a descriptive method with correlational analysis. The respondents in this study were eighth-grade students at The State Junior High School 17 Jambi City in the 2024/2025 Academic Year. The sampling technique used was random 31 students were obtained. Data were collected by distributing questionnaires to determine students' reading attitudes and conducting reading tests to assess students' reading achievement. The type of text used in this study is recount text. To measure the correlation of data, the researcher used Pearson-Product Moment using SPSS 25. The results of this study indicate that there is a low relationship between students' reading attitudes and their reading abilities